Occurrence of Lac Insect and its Host Plants in Certain Districts of Andhra Pradesh - Bhagya Priya, P.; Koteswara Rao, S. R.; Dhuruva, Sanyasi; Ramesh, D. (Indian Forester, 2025)
Survey was conducted for occurrence of lac insects, Kerria lacca Kerr. (Hemiptera: Tachardiidae) on different hosts in Bapatla (25 mandals), Guntur (17 mandals), Parvathipuram Manyam (15 mandals) and Srikakulam (30 mandals) districts of Andhra Pradesh. Occurrence of lac insects was observed in 2 mandals of Bapatla on Conocarpus lancifolius Engl. and Albizia lebbeck (L.) Benth.; in 9 mandals of Guntur on Albizia saman (Jacq.) Merr., C. lancifolius, A. lebbeck, Ficus religiosa L., Ziziphus mauritiana Lam., Annona squamosa L.; in 1 mandal of Parvathipuram Manyam on Schleichera oleosa (Lour.) and in 1 mandal of Srikakulam on Flemingia semialata Roxb.